2020
DOI: 10.1186/s40359-020-00494-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Chinese version of adjustment disorder new module-20 in breast cancer patients

Abstract: Background After the new definition of adjustment disorder (AjD) by the International Classification of Diseases-11(ICD-11), AjD has attracted more and more attention. Adjustment disorder new module-20 (ADNM-20), which is used to diagnose AjD, has been verified in some countries, but it has not been verified in China. As a result, the purpose of this study was to investigate the validity and reliability of the Chinese version of the Adjustment disorder new module-20 (ADNM-20) in female breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
2
1
1
Order By: Relevance
“…In this study, the failure to adapt and impulsivity subscales (α = 0.90 and 0.91) had the best internal consistency, and the worst comprised the anxiety and depression subscales (α = 0.72 -α and 0.69). This is similar to the ndings of two other studies that did not nd great internal consistency for anxiety and depressive moods (α = 0.61 and ω = 0.591) (23) and (α = 0.67 and α = 0.61), respectively (27).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the failure to adapt and impulsivity subscales (α = 0.90 and 0.91) had the best internal consistency, and the worst comprised the anxiety and depression subscales (α = 0.72 -α and 0.69). This is similar to the ndings of two other studies that did not nd great internal consistency for anxiety and depressive moods (α = 0.61 and ω = 0.591) (23) and (α = 0.67 and α = 0.61), respectively (27).…”
Section: Discussionsupporting
confidence: 90%
“…Another study investigating risk factors for ICD-11 AjD showed that exposure to job-or health-related stressors was signi cantly associated with ICD-11 AjD (37). While the patients in our study reported nancial stress as the most common life stressor, other researchers found it to be the second most common life stressor after a cancer diagnosis in a population of breast cancer patients (27). Health and nancial stressors interact, and cancer patients may become unable to work due to their disease diagnosis and subsequent treatment, making them feel more self-conscious and increasing the prevalence of AjD.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations